Supporting DRPs from Varied Health Science Programs. Issue 5 (24th November 2022) - Sullivan, Matthew A.; Lusk, Marie; Clifford, Grace; Gossett, Jennifer; Petersen, Kristina H.
Abstract : Rigorous health profession training programs are designed to equip students with the skills necessary to meet the needs of patients within a fast‐paced environment. Similar to medical education, allied health programs are often plagued by attitudes and mentalities rooted in ableism that may ostracize and further marginalize the very population they strive to heal.